Az európai professzionális labdarúgóklubok működési modelljeinek elemzése - Kocsis, Bence; Kiss, Csaba (Vezetéstudomány / Budapest Management Review, 2021)
The authors analysed with regard to the professional football markets the strategic patterns of the leading clubs participating in the first division leagues of UEFA’s member countries. In a sample of 54 clubs, the performance of clubs was examined along three major dimensions: financial performance, sport performance and human resource management/ transfer policy dimensions. They performed a hierarchical cluster analysis based on the classification of the clubs into four groups. These four clusters are: 1. International Elite; 2. Challengers; 3. Emerging Champions; and 4. Struggling for Competitiveness. The authors' main findings suggest that sports companies belonging to the same cluster generate a similar amount of income, are equally successful in the domestic leagues and have similar transfer policies, although each cluster differs markedly from the others.